Refleksi Mahasisawa terhadap Proses Pembelajaran dan Pengelolaan di Kelas X: Tindak Lanjut Hasil Pembelajaran di SMKN 5 Mataram - Supratman; Farianingsih; Handayani; Helniza; Maratul Iman; Azizah; Aisyah; Al Maidatul Aini; Bulansari (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Reflection on the learning process and classroom management is an important aspect of the School-Based Field Practice (PLP) activities because it can provide a realistic picture of the quality of learning implementation in schools. The urgency of this study is based on the need for continuous evaluation of the learning process in Grade X of SMKN 5 Mataram to ensure the achievement of learning objectives and the effectiveness of classroom management. This study aims to describe students’ reflections on the implementation of learning, classroom management, and the follow-up of learning outcomes applied. The method used is descriptive qualitative research. The research subjects include subject teachers and Grade X students of SMKN 5 Mataram, while the research object focuses on the learning process and classroom management. The research instruments consist of observation sheets, students’ reflection notes, and documentation of learning tools. The research procedure was carried out through stages of learning observation, reflection implementation, analysis of learning outcomes, and determination of relevant follow-up actions. The results show that the learning process was implemented in a planned manner and classroom management was relatively conducive, although students’ active participation was not yet evenly distributed. Follow-up on learning outcomes was conducted through remedial activities, material reinforcement, and learning assistance. The conclusion of this study indicates that students’ reflections are able to provide constructive evaluation of the learning process. The implications of this study are expected to serve as a basis for improving learning strategies and classroom management at SMKN 5 Mataram.